THE INFLUENCE OF PRODUCT VARIATIONS, PRICES AND SALES PROMOTIONS ON CONSUMER DECISIONS IN BUYING MITSUBISHI CARS IN SURAKARTA - M. Hasan Ma'ruf (International Journal of Economics, Business and Accounting Research (IJEBAR), 2017)
The purpose of this study was to analyze the effect of product variations, prices and sales promotions on consumer decisions in buying Mitsubishi cars in Surakarta both partially and partially. The data analysis techniques used are validity test, reliability test, classic assumption test, multiple linear regression analysis, t test, F test, coefficient of determination (R²). The results obtained: 1) The results of the t test obtained product variations have a positive and significant effect on purchasing decisions, the price has a positive and significant effect on purchasing decisions and promotion has a positive and significant effect on purchasing decisions, 2) F test results obtained Sig. amounting to 0,000 smaller than 0.05 or sig. = 0.000